Water Reserves for the Environment: A Strategic and Temporal Analysis (2012–2022) for the Implementation of Environmental Flows in Mexico - Sergio A. Salinas-Rodríguez; Anuar I. Martínez Pacheco (Diversity, 2024)
In Mexico, the evaluations of environmental flows are regulated by the Mexican Norm NMX-AA-159-SCFI-2012, and they warrant the establishment of water reserves for the environment. However, the pressure or demand for water use limits the establishment of said reserves because their implementation is generally conditioned to water availability. This research aimed to evaluate the changes through time of the variables that serve as a basis for the implementation strategy by the Mexican government. A geographical information system was built with updated information on water availability, conservation values, and pressures for all basins nationwide. Their desired conservation status was analyzed, and the potential reserves were estimated based on the reference values. The results were examined according to the ranking changes in environmental water reserves enactment feasibility and desired conservation status of Mexican basins, the progress achieved to date, and the potential contribution to the conservation of protected areas and their connectivity if the gaps of reserves were implemented. The outcomes point towards an administrative implementation strategy with positive results despite the growing demand for water use, with a change rate higher than the one for the creation of new protected areas. Currently, basins with low demand and high conservation value have the potential to meet people’s and the environment’s water needs, and contribute to 86% of the goal set by the present administration without affecting water availability. Finally, reserving water in the priority basins would guarantee the legal protection of the flow regime in 48–50% of the hydrographic network (63,760–66,900 km) in a desired conservation status, 43–49% of wetlands of international importance (48,650–49,600 km2) and other protected areas (128,700–136,500 km2) in 85–89% of the global ecoregions represented in Mexico (780,500–852,200 km2).